Migration, EU integration and the Balkan Route - Kmezić, Marko 1977-; Prodromidou, Alexandra; Gkasisv, Pavlos (Southeast European Studies, 2024)
"Contributing to our understanding of the impact of the 2015 migrant ‘crisis’ on the future of EU integration, this book views the ‘crisis’ as an accelerant to existing problems, namely Brexit, the growing popularity of anti-immigrant far right parties, and the rise of xenophobic and antiliberal governments from the Baltics to the Balkans. Providing analysis at the national, regional level and EU level, this book shows how the countries on the migrant route have been affected according to their degree of integration with the EU and the specific socio-political and economic conditions of each country. The volume will be of interest to scholars or international relations, security studies, border studies, EU policies, migration studies and Southeast European studies."